Analysis of dispersion characteristics of solid-core PCFs with different types of lattice in the claddings, infiltrated with ethanol - Le Tran, Bao Tran; Thi, Thuy Nguyen; Thi Minh, Ngoc Vo; Canh, Trung Le; Van, Minh Le; Long, Van Cao; Xuan, Khoa Dinh; Chu, Lanh Van (Photonics Letters of Poland, 2020)
In this paper, we propose three solid-core photonic crystal fibers based on silica, with hexagonal, circular and square lattices as a cladding, composed of 8 rings of air-holes surrounding the core, infiltrated with ethanol. Using a commercial software we simulated the light propagation in these structures. The size of the air-holes was from 1 µm to 4 µm. We have shown that the fibers with the hexagonal lattices are optimal for supercontinuum generation since their dispersion characteristics are flat and the smallest.